Strategi dan Implementasi dalam Pengawasan dan Pengendalian Narkotika dalam Lembaga Pemasyarakatan - Putra, I Komang Wahyu Mahardana; Fakhlur (HUMANIORUM, 2025)
Indonesian Correctional Institutions, commonly referred to as "Lapas," serve crucial roles in rehabilitating and supervising inmates, initially known as prisons. Operated under the Directorate General of Corrections, Ministry of Law and Human Rights, these institutions enforce laws such as Act No. 12 of 1995 on corrections, addressing inmate rights and rehabilitation but limitedly covering female inmates. The misuse of narcotics, posing significant societal risks, demands stringent control measures within these facilities due to their potential misuse and profound impact on young generations and societal stability. The collaborative efforts between law enforcement and correctional facilities are crucial for managing and curtailing the illicit drug trade within these confines. This qualitative study explores the normative legal framework applying to narcotics management in correctional settings, involving comprehensive literature reviews and analysis of primary and secondary data sources. The findings reveal that narcotics trafficking within prisons is often facilitated by both inmates and visitors, utilizing methods such as concealing drugs in food or personal belongings. Factors enabling these practices include inadequate security infrastructure like the absence of X-ray machines and insufficient guard training. To combat these challenges, correctional facilities have implemented enhanced security measures, rigorous personnel training, and systematic drug screening processes.